Alkali‐Stable Metal–Organic Frameworks with Enhanced Electroconductivity for Black‐Brown Electrochromic Energy Storage Smart Window - Xinyi Wang; Zhiqiang Liu; Heqi Ma; Yiwen Liu; Qing Sui; Jifei Feng; Guofa Cai (Advanced Science)
Abstract Metal–organic frameworks (MOFs) deliver potential applications in electrochromism and energy storage. However, the poor intrinsic conductivity of MOFs in electrolytes seriously hampers the development of the above‐mentioned electrochemical applications, especially in one MOF electrode. Herein, a new Ni‐based MOF (denoted Ni‐DPNDI) is proposed with enhanced conductivity by π‐delocalized DPNDI connectors. Predictably, the obtained Ni‐DPNDI MOF achieves a conductivity of up to 4.63 S∙m−1 at 300 K. Profiting from its unique electronic structure, the Ni‐DPNDI MOF delivers excellent electrochromic and energy storage performance with a great optical modulation (60.8%), a fast switching speed (tc = 7.9 s and tb = 6.4 s), a moderate specific capacitance (25.3 mAh·g−1) and good cycle stability over 2000 times. Meanwhile, energy storage capacity is visual by the coloration states of Ni‐DPNDI film. As a proof of the potential application, a large‐area (100 cm2) electrochromic energy storage smart window is further designed and displayed. The strategy provides an interesting alternative to porous multifunctional materials for the new generation of electronic devices with diverse applications.